2018
DOI: 10.29312/remexca.v3i1.1485
|View full text |Cite
|
Sign up to set email alerts
|

Relación nitrato/amonio/urea y concentración de potasio en la producción de tomate hidropónico

Abstract: Plantas de tomate (Solanum lycopersicum L. cv. IB-9) fueron cultivadas en un sistema hidropónico con el objetivo de evaluar el efecto de la relación nitrato, amonio, urea (100/0/0, 85/15/0, 85/0/15 y 85/7.5/7.5) y la concentración de potasio (7 y 9 mol m-3) en el rendimiento de fruto y composición mineral de las plantas. El rendimiento de fruto no fue afectado por los tratamientos, por lo que se puede sustituir 15% del total de nitrógeno nítrico de la solución nutritiva con un porce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…Al aumentar la acidez del suelo se incrementa la actividad del hierro y del aluminio, en esta forma los fosfatos solubles quedan fijados como compuestos complejos e insolubles de hierro y aluminio (Sanguino, 1961), por lo tanto, se disminuye la cantidad de fósforo disponible para las plantas con alto nivel de amonio. Caso contrario ocurre en un sistema hidropónico que reportó Parra et al (2012), en donde al aplicar una mayor concentración de amonio (15 %) con la solución nutritiva de 8…”
Section: Resultados Y Discusiónunclassified
“…Al aumentar la acidez del suelo se incrementa la actividad del hierro y del aluminio, en esta forma los fosfatos solubles quedan fijados como compuestos complejos e insolubles de hierro y aluminio (Sanguino, 1961), por lo tanto, se disminuye la cantidad de fósforo disponible para las plantas con alto nivel de amonio. Caso contrario ocurre en un sistema hidropónico que reportó Parra et al (2012), en donde al aplicar una mayor concentración de amonio (15 %) con la solución nutritiva de 8…”
Section: Resultados Y Discusiónunclassified
“…Parra- Terraza et al (2012) also note that an increase of Ca 2+ in the nutrient solution is not reflected in production but only in tissue analysis. The mineral content being higher in the treatments whit high dose on agrees with Turkment et al (2008) who reported lower K content in the control that showed the lowest quality of chili plant, independent of the source of potassium (Chapagain et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Nutrient solutions were adjusted to an osmotic potential of -0.072 Mpa. The concentrations of K + , Ca 2+ and Mg 2+ remained constant (Steiner, 1984;Parra-Terraza et al, 2012), maintaining constant concentrations of NO 3 -, H2PO 4 -and SO 4 2-(Ramí rez et al, 2010). Nine nutrient solutions were defined, at three levels of %K + (27, 35, and 43), with three levels of %Ca +2 (37, 45, and 53), these nine nutrient solutions were applied simultaneously in four replicates inside the shade house to account as a blocks.…”
Section: Methodsmentioning
confidence: 99%
“…Stem thickness is an indicator of the vigorous state of a seedling since it directly reflects the accumulation of photosynthates, which can be transferred to demand sites (Parra-Terraza et al, 2010). Fernández-Bravo et al (2006), evaluated the emergence of tomato seeds in different substrates (peat moss, compost, coconut sawdust) and obtained values for the variable stem thickness from 0.9 to 1.3 mm.…”
Section: Stem Thicknessmentioning
confidence: 99%
“…This variable was also adjusted to a logistic growth model proposed by Hunt (2017) (Table 6) and, according to the results, there were significant differences between the different substrates evaluated; as can be seen, the seedlings that presented more leaves were those that were sown in peat moss and tezontle, highlighting treatments 5 (T + 100) and 8 (P + S100) in which an average of 5 leaves per seedling were counted, on the other hand, the substrates based on vermicompost and coconut fiber showed the lowest values, 3 and 2 leaves respectively, this also due to the fact that in these substrates the seedlings took longer to emerge (Figure 4). -Terraza et al (2010) mention that the number of leaves is a valuable indicator in terms of the quality of the seedlings, and that in the case of tomato, the seedlings must present 6 to 7 leaves at the time of transplantation. Regarding the nutrient solution applied, there were no significant differences (Table 3); however, the number of leaves was favored when applying the 100% nutrient solution (Figure 4).…”
Section: Number Of Leavesmentioning
confidence: 99%